Differences and similarities of proliferative and non-proliferative forms of biopsy-proven lupus nephritis: Single centre, cross-disciplinary experience. (August 2022) - Duran, Emine; Yıldırım, Tolga; Taghiyeva, Arzu; Bilgin, Emre; Arıcı, Mustafa; Sağlam, Emine Arzu; Özen, Seza; Üner, Meral; Erdem, Yunus; Kalyoncu, Umut; Ertenli, Ali Ihsan
Objective: We aimed to compare clinical features, outcomes, treatments, and to define the predictive factors of complete renal response (CRR) in patients with proliferative and non-proliferative lupus nephritis (LN). Methods: Patients with systemic lupus erythematosus (SLE) followed between 2014 and 2020 at Hacettepe University Hospitals and who had a kidney biopsy were the subject of the study. One hundered and sixteen patients' kidney biopsies reported as LN were evaluated retrospectively. Clinical characteristics and laboratory values at the time of kidney biopsy, histopathological forms of LN, and renal response (complete or partial) were recorded. We analyzed the association between CRR rates during the 2-year follow-up after induction therapy and the predictive factors for CRR. Results: Of 116 (93 females, 23 males) patients, 95 (81.9%) were in the proliferative group (class III and IV) and 21 (18.1%) were in the non-proliferative group (class II and V). In the proliferative group, the percentage of the patients with elevated basal creatinine levels, median daily proteinuria, anti-double-stranded DNA (dsDNA) positivity, low C3 and C4 levels, the presence of active urinary sediment, and median renal SLE Disease Activity Index (SLEDAI) scores at the time of kidney biopsy were significantly higher than the non-proliferative group. Renal response status during the 2-year follow-up after induction therapy was available for 99 patients. During this time, 70 (70.7%) patients had achieved CRR and time-to-CRR was similar between the proliferative and non-proliferative groups (p = 0.64, log-rank test). The Cox proportional hazards model showed that achievement of CRR was associated with female gender [HR: 2.15 (1.19–3.89 95% CI), p = 0.011], newly diagnosed SLE with renal biopsy [HR: 2.15 (1.26–3.67 95% CI), p = 0.005], hypertension [HR: 0.40 (0.27–0.94 95% CI), p = 0.032], eGFR increase [HR: 1.01 (1.00–1.01 95% CI), p = 0.046], and the presence of active urinary sediment [HR: 0.46 (0.22–0.96 95% CI), p = 0.039]. Conclusions: Achieving CRR was similar in proliferative and non-proliferative LN patients, although certain laboratory parameters differed at the onset. Our results indicated the importance of kidney biopsy in the decision-making of treatment of SLE patients with renal involvement and that the defined factors associated with CRR achievement help to predict good renal response.